Growth Performance and Productivity of Several Soybean Genotypes (Glycine max L. Merr.) Cultivated at High Altitude Areas in Indonesia. - Lubis, Iskandar; Atmaja, Ian Surya Fitra; Koesoemaningtyas, Tri; Ghulamahdi, Munif; Purnamawati, Heni; Shiraiwa, Tatsuhiko (Journal of Tropical Crop Science, 2021)
The low productivity of soybeans (Glycine max) and the impacts of climate change have led to the need for adaptive varieties to high altitude to produce high yields. In this study, nine soybean genotypes from different geographic regions, tropical and subtropical, were tested. The aim of the research was to investigate the growth and productivity of different genotypes of soybean when grown in high-altitude environment. Results showed that the tropical genotypes, “Tanggamus” and “SC-1-8” from Indonesia, “Manshuu-masokutou” from China, and “San Sai” from Thailand, had longer growth duration than the subtropical genotypes, “Enrei” and “Fukuyutaka” from Japan, “Stressland” and “Ht-2” from the United States, and “Hakubi” from China. Tropical genotypes have greater growth values than subtropical genotypes as shown by taller plants, greater number of leaves and dry weight. Among the tropical genotypes, “SC-1-8”, which is a soybean line from IPB, showed the best growth rates and competitive crop yield, making it a potentially good candidate for high yielding soybean in Indonesia.